The relationship between depression, anxiety and visual reaction times in athletes - Yavuz, H. U.; Oktem, F. (Biology of Sport, 2012)
The aim of the study was to evaluate depression, state and trait anxiety scores and visual reaction times, and to define the impact of these variables on each other in swimmers and track and field athletes. One hundred athletes participated in this study including 25 female and 25 male national level swimmers and track and field athletes. Application of Spielberger`s State-Trait Anxiety Inventory, Beck Depression Inventory (BDI) and Donder`s Reaction Time Test to all participants revealed no significant relationship among obtained data except for a correlation between state and trait anxiety and depression scores (r =0.53, r=0.73 respectively, p<0.001). The mean trait anxiety score in female athletes was higher than that in males (42.60 ± 8.04 and 38.66 ± 7.13 respectively, p<0.05), whereas no gender differences were found for simple, choice or recognition reaction times and depression or state anxiety scores. Even though clinical depression and anxiety may affect the reaction times in patients, these results suggest that there is no correlation between anxiety and depression scores and reaction times in healthy athletes.